Chapter 11 Democracy-Driven Governance and Governance-Driven Democratisation in Barcelona and Nantes - Bua, Adrian (Taylor & Francis, 2023)
Bua and Bussu's (2021) article charted transitions between democracy-driven and governance-driven institutional reforms in the case of Barcelona. Their work is useful in identifying dynamism and tipping points shifting between elite-led and bottom-up forms of democratic governance. Building on this work, this chapter adds comparative analytical leverage to Bua and Bussu's insights by comparing the paradigmatic cases of "democracy-driven governance" in Barcelona (Spain) and "governance-driven democracy" in Nantes (France). Based on an analytical framework derived from previous work explaining the institutionalisation of participatory governance (Bussu 2012; Fung and Wright 2003; Heller 2001), the chapter develops knowledge as to the conditions under which DDG-like forms of participatory governance develop, flourish and are sustained or undermined. Nantes and Barcelona are appropriate cases because they have governance histories and contextual features but vary on the recent development of DDG in Barcelona and the sustenance of GDD in Nantes. This chapter explains this divergence, seeking to identify conditions that support DDG.